Thematic Analysis of The Role of Zakat In Improving Economic Welfare (Case Study: BAZNAS Bogor) - Hija, Liya Nabilatul; Akbar, Nashr (Fakultas Agama Islam, Universitas Ibn Khaldun Bogor, 2025)
This research aims to analyze the role of zakat in empowering local economy through strategic management of zakat by BAZNAS Bogor. A reflexive thematic analysis by Braun and Clarke has been adopted as a research method supported by NVivo 15 software. Data was collected from 13 journal articles from the Dimension database that met the predetermined criteria to be analyzed in this research. The results found that BAZNAS Bogor has implemented various programs to empower the socio-economy of mustahiq. These programs have shown positive impacts on income growth and business sustainability of mustahiq. Several key themes have been identified as the driving factors of the success of BAZNAS in improving the role of zakat in economic empowerment, including transparency, cooperation with the government, effective distribution mechanism, targeted program, and strong supervision. These results provide insights into zakat institutions on how to improve the economic welfare of mustahiq. As a policy recommendation, BAZNAS is advised to integrate empowerment programs with a digital data-based monitoring and evaluation system to ensure the effectiveness and sustainability of social interventions.